For Want of a Cup: The Rise of Tea in England and the Impact of Water Quality on Mortality - Francisca M. Antman (Institute of Labor Economics (IZA), 2022)
This paper explores the impact of water quality on mortality by exploiting a natural experiment. the rise of tea consumption in 18th century England. This resulted in an unintentional increase in consumption of boiled water, thereby reducing mortality rates. The methodology uses two identication strategies tying areas with lower initial water quality to larger declines in mortality rates after tea drinking became widespread and following larger volumes of tea imports. Results are robust to the inclusion of controls for income and access to trade. The hypothesis is further bolstered by suggestive evidence from cause-specific deaths and early childhood mortality.
Keywords: N33; I15; Q25; Q56; 330; tea; water quality; mortality; Industrial Revolution